Are observer ratings of applicants' personality also faked? Yes, but less than self‐reports1. (June 2017) - König, Cornelius J.; Steiner Thommen, Larissa A.; Wittwer, Anne‐Marie; Kleinmann, Martin
Abstract: Although self‐report personality tests are a comparatively cheap and easy‐to‐administer personnel selection tool, researchers have criticized them for not predicting enough criterion‐related variance. Researchers have suggested using observer‐ratings of personality (e.g., as part of a reference check from a supervisor) because observer‐ratings have been reported to be more predictive. However, it is theoretically and empirically unclear whether supervisors also engage in faking (the intentional distortion of responses). Study 1 explored faking among managers who were first asked to imagine that a subordinate had to leave his/her job for private reasons and then to rate the personality of the subordinate. A week later, managers rated their subordinates honestly. A repeated‐measures MANOVA indicated that managers did fake. Study 2 (among supervisors of working students) replicated the above findings but also showed that there is less faking in supervisor‐ratings than in self‐ratings. Furthermore, we found no evidence that the validity of personality scales for predicting academic performance depends on self‐ versus observer‐ratings or on an applicant versus an honest condition. These two studies thus show that practitioners should not equate personality ratings obtained from observers in a selection context with honest personality ratings.